Experimental evaluation of fish feeder machine controller system - Mohd Yusoff, Ainul Husna; Md Salleh, Salihatun; Abdullah, Mohd Ezree; Zaman, Izzuddin; Md Hani, Mohd Hatta; Siswanto, W.A.; Wan Mahmud, Wan Azlan (Penerbit UTHM, 2018)
The aim of this project is to apply the automatic fish feeder controller system for fish pellet dispersion machine. The system uses Arduino as a microcontroller which programmed by setting the speed and timer of each DC motor to make this machine functioning automatically. When the adapter is switch, the microcontroller will be connected then activate the motor driver to generate the system. Two motors have been used as motor 1 and motor 2 which functions to drop and disperse the fish pellet respectively. The whole system was programmed through a specific coding and uploaded to the Arduino. This project benefits in reduce the manpower for the fish farming. The component that required to build this project is portable and cost-effective. From experimental result, the timer for motor 1 to dispense the fish food from the storage was 60s while 90s for DC motor 2 as a distributor. The speed for motor 1 was set to 110rpm while motor 2 was set with full speed of 255rpm. The fish pellet can be distributed and scattered up to 5m which can reduce the competition among the fish at one place.